Fixed-Dose Lisdexamfetamine More Effective Than Methylphenidate in Adolescents With ADHD - Bittner, Dennis (MD Conference Express, 2015)
Lisdexamfetamine dimesylate was statistically superior to osmotic controlled-release methylphenidate in a forced-dose study of adolescents with attention-deficit/hyperactivity disorder but failed to meet standards of statistical significance in a flexible-dose version of the study.